Salmonella spp investigation in transport boxes of day-old birds - Zancan, F. T.; Berchieri, A.; Fernandes, S. A.; Gama, NMSQ (Soc Brasileira Microbiologia, 2000)
The presence of Salmonella was investigated in transport boxes of newly hatched chicks in the moment they were received in the farms. 1,611 boxes, delivered to 15 farms (one broiler grand-parent farm, four broiler parent farms, two commercial broiler chick farms and seven laying hens farms) were tested. A total of 19 visits to these farms were done, and Salmonella was detected in ten of these visits. Salmonella Heidelberg was detected in boxes in five farms. S. Heidelberg and S. Mbandaka were simultaneously detected in one broiler breeder farm. Salmonella Enteritidis alone, S. Enteritidis and S. Mbandaka and S. Cerro alone were detected in three, one and one laying hens farms, respectively.
Keywords: Salmonella; day-old bird; transport box